The Influence of Exports, Imports, and Exchange Rates on the Economic Growth of the Riau Islands Province 2010-2023 - Dini Erawati Hutagalung; Tasha Zania; Gina Septiana (CAKRAWALA : Management Science Journal, 2024)
This research aims to find out the influence of exports, imports and exchange rates on economic growth in the Riau Islands in 2010-2023. This research uses a quantitative research method. This research uses secondary data in the form of a time series from 2010-2023 which includes the variables of economic growth, exports, imports and exchange rates. This data was obtained from the Badan Pusat Statistik and Bank Indonesia. Using Multiple Linear Regression Analysis using the Classic Assumption Test, then testing the model using the T Statistical Test and the F Statistica Test which were estimated using the SPSS version 25.0 program. Based on the research results, exports have a positive and significant effect on economic growth in the Riau Islands Province, imports do not have a significant effect on economic growth in the Riau Islands Province, and the exchange rates has a negative and significant effect on economic growth in the Riau Islands Province.